Visual problems associated with traumatic brain injury. (28th February 2018) - Armstrong, Richard A
Abstract : Traumatic brain injury (TBI) and its associated concussion are major causes of disability and death. All ages can be affected but children, young adults and the elderly are particularly susceptible. A decline in mortality has resulted in many more individuals living with a disability caused by TBI including those affecting vision. This review describes: (1) the major clinical and pathological features of TBI; (2) the visual signs and symptoms associated with the disorder; and (3) discusses the assessment of quality of life and visual rehabilitation of the patient. Defects in primary vision such as visual acuity and visual fields, eye movement including vergence, saccadic and smooth pursuit movements, and in more complex aspects of vision involving visual perception, motion vision ('akinopsia'), and visuo‐spatial function have all been reported in TBI. Eye movement dysfunction may be an early sign of TBI. Hence, TBI can result in a variety of visual problems, many patients exhibiting multiple visual defects in combination with a decline in overall health. Patients with chronic dysfunction following TBI may require occupational, vestibular, cognitive and other forms of physical therapy. Such patients may also benefit from visual rehabilitation, including reading‐related oculomotor training and the prescribing of spectacles with a variety of tints and prism combinations.